LITERATION : ACEHNESS SEDATI ONE DAY FOR TEACHER - Sephia Dini Pratiwi Tiwi (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
ABSTRACT This study is a descriptive qualitative method that raises the phenomenon of literacy or habits related to Acehnese culture. This study aims to provide information related to culture that is currently trending and implemented by teachers, especially elementary schools in Aceh. The